2019
DOI: 10.1007/s11442-019-1587-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of Qinghai Lake ice phenology between 2000 and 2016

Abstract: Lake ice phenology is considered a sensitive indicator of regional climate change. We utilized time series information of this kind extracted from a series of multi-source remote sensing (RS) datasets including the MOD09GQ surface reflectance product, Landsat TM/ETM+ images, and meteorological records to analyze spatiotemporal variations of ice phenology of Qinghai Lake between 2000 and 2016 applying both RS and GIS technology. We also identified the climatic factors that have influenced lake ice phenology ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The freezing temperature of Qinghai Lake is slightly lower than 0 • C. It usually freezes in mid-December each year and completely freezes in early January of the following year. The frozen Qinghai Lake begins to melt in mid-to late March and is completely melted by early April [31]. Ice thickness is on average 50 cm, and the maximum ice thickness is 70 cm [32].…”
Section: Study Areamentioning
confidence: 99%
“…The freezing temperature of Qinghai Lake is slightly lower than 0 • C. It usually freezes in mid-December each year and completely freezes in early January of the following year. The frozen Qinghai Lake begins to melt in mid-to late March and is completely melted by early April [31]. Ice thickness is on average 50 cm, and the maximum ice thickness is 70 cm [32].…”
Section: Study Areamentioning
confidence: 99%
“…Previous studies reported that latitude, surface area, volume, depth, salinity, air temperature, and precipitation are factors influencing lake ice phenology [12,19,26,30,35,36,84]. The quantitative relationships between lake ice phenology parameters and these factors were analyzed by linear regression, and the significance of these relationships was also calculated using the F-test with p < 0.05, p < 0.01, and p < 0.001.…”
Section: Driving Factorsmentioning
confidence: 99%
“…1 and Table B.8 (Appendix B). While most of the earlier works (Gou et al, 2015;Qi et al, 2019Qi et al, , 2020Yao et al, 2016) on long time-series monitoring of lake ice with MODIS concentrated on larger lakes, many lakes that freeze are actually small-or medium-sized mountain lakes, especially outside the (sub-)Arctic regions. The lakes we analyse are relatively small in area (0.78 -11.3 km 2 ), representative for this category.…”
Section: Study Areamentioning
confidence: 99%